2011
DOI: 10.1007/s00420-011-0689-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between psychosocial work environment, attitudes towards older workers (ageism) and planned retirement

Abstract: Ageism, lack of recognition and lack of development possibilities are associated with older male workers' retirement plans in our analyses. Workability has the strongest association with retirement plans for both genders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 35 publications
4
71
1
1
Order By: Relevance
“…a certain age range, can easily lead to generalisations and stereotyping [114]. Age discrimination has significant associations with early retirement, 15 especially for men [115]. However, age discrimination appears to be more common for women.…”
Section: Attitude Of Managers and Organisationsmentioning
confidence: 99%
“…a certain age range, can easily lead to generalisations and stereotyping [114]. Age discrimination has significant associations with early retirement, 15 especially for men [115]. However, age discrimination appears to be more common for women.…”
Section: Attitude Of Managers and Organisationsmentioning
confidence: 99%
“…While some workers welcome retirement, retiring effectively cuts off a wellspring of social connections, opportunities, and meaning available on a day-to-day basis. Early retirement -which can be catalyzed by the experience of ageism at the workplace (Thorsen et al 2012;von Hippel et al 2013) -can be particularly pernicious to older adults' cognition and mental health (Börsch-Supan and Schuth 2014). Börsch-Supan and Schuth (2014) found that retirement in general, and early retirement in particular, are associated with reductions in overall social network size, and that this reduction is mostly owing to the presence of fewer friends, colleagues, and other non-family contacts in one's social network.…”
Section: Social Exclusionmentioning
confidence: 99%
“…During September-December 2008, 12 584 Danish residents responded to the DANES survey (response rate 69%) (21,22). We invited these respondents to participate in PEWED if they (i) were between 18-65 years, (ii) were employed, (iii) responded by mailed or internet questionnaire, but not by telephone interview, as mode of administration can affect the answers (23), and (iv) had depressive symptoms, defined as a score of ≥10 points on the Major Depression Inventory (MDI) (24,25).…”
Section: Study Design and Populationmentioning
confidence: 99%